LEGAL PROTECTION OF COSMETICS NON-HALAL LEBEL COSMETICS IN TERMS OF THE SALE AND PURCHASE CONTRACT - Shalihah, Nurul Imratu (JURISTA: Jurnal Hukum dan Keadilan, 2017)
The use of cosmetics has become commonplace for Indonesian women. However, the use of non-halal labelled products from the practice of buying and selling cosmetics is still widely seen among the public, especially in Banda Aceh. This research was raised with the title of Legal Protection for the People of Banda Aceh City in Wearing Non-Halal Label Cosmetics in Review of the Sale and Purchase Agreement. This research aims to answer 3 research questions, namely how the form of legal protection for consumers who use non-halal cosmetic products, how the form of use of non-halal label cosmetic products, and how the perspective of Islamic law on the legal protection of non-halal label cosmetic consumers in the city of Banda Aceh. The research method used is descriptive analysis, namely data collection techniques in the form of field and literature studies. The results of this study indicate that the form of legal protection for consumers who use non-halal labelled cosmetic products carried out by the Banda Aceh city government is by imposing jinayah sanctions. Both in the form of flogging, imprisonment, and fines in accordance with Aceh Qanun Number 8 of 2016 concerning the Halal Guarantee System. The form of use of non-halal labelled cosmetic products in the people of Banda Aceh city varies, namely Special UV whitening, bb cream night and day, Doolby lipstick, make over, and so on. This product is used for skin beauty on the face, hands and body. The perspective of Islamic law on legal protection for consumers of non-halal labelled cosmetics in the city of Banda Aceh in the sale and purchase contract must be carried out so that consumers are protected from buying and selling which contains elements of lies about the goods they buy, especially from elements that are not halal for use by buyers. From the results of this study, the author suggests that the Banda Aceh city government continue to take firm steps in the circulation of non-halal labelled products. In addition, buyers must also be more careful in choosing cosmetics that will be used daily.